Overgeneral past and future thinking in dysphoria: the role of emotional cues and cueing methodology. Issue 5 (27th May 2016) - Anderson, Rachel J.; Boland, Jennifer; Garner, Sarah R.
Abstract : Overgeneral memory, where individuals exhibit difficulties in retrieving specific episodes from autobiographical memory, has been consistently linked with emotional disorders. However, the majority of this literature has relied upon a single methodology, in which participants respond to emotional cue words with explicit instructions to retrieve/simulate specific events. Through the use of sentence completion tasks the current studies explored whether overgenerality represents a habitual pattern of thinking that extends to how individuals naturally consider their personal past and future life story. In both studies, when compared with controls, dysphoric individuals evidenced overgeneral thinking style with respect to their personal past. However, overgeneral future thinking was only evident when the sentence stems included emotional words. These findings highlight the importance of investigating the overgenerality phenomenon using a variety of cueing techniques and results are discussed with reference to the previous literature exploring overgenerality and cognitive models of depression.